Bacterial N‐formyl Peptides Reduce PMA‐ and Escherichia coli‐Induced Neutrophil Respiratory Burst in Term Neonates and Adults. (May 2017) - Stålhammar, M. E.; Douhan Håkansson, L.; Sindelar, R.
Abstract: Neutrophil migration and respiratory burst are the prerequisite for efficient first line defense against invading microorganisms. However, migration and respiratory burst can be compromised in adults and especially in newborn infants, where sustained neutrophil accumulation, uncontrolled burst and reduced scavenging of ROS might cause inadvertent tissue damage due to uncontrolled inflammation. The aim of this study was to investigate the modulatory effect of the chemoattractants formyl‐methionyl‐leucyl‐phenylalanine (fMLP) and IL‐8 on respiratory burst in neutrophils from term newborn infants and adults. Whole blood from the umbilical cord of 17 healthy term newborn infants delivered by caesarean section and from 17 healthy adults as reference was preincubated with fMLP or IL‐8 and stimulated with PMA or Escherichia coli bacteria. Respiratory burst was quantified by flow cytometry analysis of dihydrorhodamine 123 fluorescence. fMLP reduced the PMA‐induced respiratory burst of neutrophils from newborn infants and adults by 12% and 21%, respectively ( P < 0.05). E. coli ‐induced burst was also reduced by fMLP in neutrophils from newborn infants (10%; P < 0.01) and adults (6%; P < 0.05). No such changes were observed with IL‐8. Similar respiratory burst in response to single stimulus with PMA or E. coli was observed in both newborn infants and adults. fMLP reduced PMA‐ and E. coli ‐induced respiratory burst of neutrophils in whole blood from term newborn infants as well as in adults. The reduced respiratory burst by fMLP might be a mechanism to reduce the detrimental effects of uncontrolled inflammation during neutrophil migration.